A novel principle for improving collapse resistance of steel frame structures. (September 2022) - Qiao, Huiyun; Xia, Jian; Chen, Yu; Chen, Canwen; Zheng, Juhuan
Abstract: Although the reduced beam section (RBS) connection is an excellent seismic design for transferring plastic hinge, it is prone to fracture under the condition of large deformation. In addition to good seismic response, the performance of RBS connections needs to be improved to ensure good anti-progressive collapse response. In this study, a novel principle is proposed, in which the RBS connection is used to meet the plastic hinge transmission, and kinked reinforced bars are installed in the beam–column connection to realize a second path. Experimental and numerical investigations were conducted on a frame substructure with kinked reinforced bars, considering their diameter d, kinked height a and length l of the reinforced bars. The deformation capacity, vertical force vs. deformation response, failure mode, and contributions of the flexural and catenary actions on the reinforced bars were evaluated. The test results demonstrate that the kinked reinforced bars started to work when the reduced-beam-section connection with reinforced bars (RRBS) is in a plastic state. When the reinforced bars with a  > 1.5 d were installed at the beam end, the bearing capacity of the RRBS specimens increased with an increase in the diameter d and decreased with an increase in the length l of the reinforced bars. In addition, When the cracking first occurred at the reduced section, the bearing capacity decreased with an increase in the kinked height a . It is suggested to select the kinked height of the reinforced bar according to the deformation capacity of the beam. Highlights: Tests on a novel principle with kinked reinforced bars are reported. Specimens include bars with various diameters, kinked heights, and lengths. Various fracture and failure modes occurred in the connection types. The effect of the reinforced bars on catenary is proved to be considerable. The kinked height should match the deformation capacity during beam cracking.